2008
DOI: 10.1086/524648
|View full text |Cite
|
Sign up to set email alerts
|

The CO Molecular Outflows of IRAS 16293−2422 Probed by the Submillimeter Array

Abstract: We have mapped the protobinary source IRAS 16293À2422 in CO 2Y1, 13 CO 2Y1, and CO 3Y2 with the Submillimeter Array (SMA). The maps with resolution of 1.5 00 Y5 00 reveal a single small-scale ($3000 AU ) bipolar molecular outflow along the east-west direction. We found that the blueshifted emission of this small-scale outflow mainly extends to the east and the redshifted emission to the west from the position of IRAS 16293A. A comparison with the morphology of the large-scale outflows previously observed by si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 33 publications
11
74
0
Order By: Relevance
“…While further observations of these sources are needed to assess the exact nature of the millimeter continuum emission, it is likely that the emission is due to a blend of free-free emission (from the shock) and dust continuum emission (from the local accumulation of material). The bright CO emission detected in Knots A and B might also come from column density enhancement and/or heating of the gas, similar to what was observed towards IRAS 16293 by Yeh et al (2008), and towards HH 46 by van Kempen et al (2010) thanks to high-J CO lines emission. Complementary molecular observations are needed to confirm the exact physical processes (shocks, photon heating) responsible for both the CO and continuum emission towards these sources.…”
Section: Nature Of the Detected Sourcessupporting
confidence: 78%
“…While further observations of these sources are needed to assess the exact nature of the millimeter continuum emission, it is likely that the emission is due to a blend of free-free emission (from the shock) and dust continuum emission (from the local accumulation of material). The bright CO emission detected in Knots A and B might also come from column density enhancement and/or heating of the gas, similar to what was observed towards IRAS 16293 by Yeh et al (2008), and towards HH 46 by van Kempen et al (2010) thanks to high-J CO lines emission. Complementary molecular observations are needed to confirm the exact physical processes (shocks, photon heating) responsible for both the CO and continuum emission towards these sources.…”
Section: Nature Of the Detected Sourcessupporting
confidence: 78%
“…The SiO channel maps by Jørgensen et al (2011) show that the SiO emission is both blue-and red-shifted, and SMA maps of CO J = 2−1 and J = 3−2 show that there is significant blue-shifted emission towards source B (Takakuwa et al 2007;Yeh et al 2008). These observations corroborate the scenario that the arch is an active shock region.…”
Section: Discussion: Origin Of the Emissionsupporting
confidence: 67%
“…The log of the observations, beam sizes and noise levels are summarized in Table 1. Previous papers by Yeh et al (2008) and Bisschop et al (2008) presented part of these data from 2005 Feb. 18, focusing on the CO outflow emission and selected complex organic molecules, respectively.…”
Section: Observationsmentioning
confidence: 99%
“…This led these authors to suggest that the IRAS 16293B in fact was the older of these two sources -possibly a low luminosity T Tauri star. This view has, however, been challenged by high resolution CO observations showing that the East-West outflow is unambiguously associated with IRAS 16293A (e.g., Yeh et al 2008). On the smallest scales in the system, it remains an important question if the outflows play a role in regulating the temperature and density structure: through the high angular resolution CO 2-1 and 3-2 maps Yeh et al (2008) for example showed the existence of two bright spots in their outflow maps offset by about 1 from the two protostars and toward IRAS16293A in particular, Chandler et al (2005) showed that excitation transitions of a number of other species were offset likely due to the impact of this outflow (in particular, their Fig.…”
Section: The Importance Of the Outflows In Iras 16293-2422mentioning
confidence: 99%